2016
DOI: 10.1111/bph.13486
|View full text |Cite
|
Sign up to set email alerts
|

Possible role for anisodamine in organophosphate poisoning

Abstract: In cases of organophosphate poisoning, patients are treated with a combination of antidotes. In addition to these poison‐directed antidotes, patients may require extra oxygen and artificial ventilation; other modalities may also be needed due to the wide range of toxic effects. Anisodamine is a belladonna alkaloid, and like other drugs from this family is non subtype‐selective muscarinic, and a nicotinic cholinoceptor antagonist, which has been employed in traditional Chinese medicine. As a muscarinic antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 87 publications
(160 reference statements)
0
16
0
Order By: Relevance
“…Anisodamine is a belladonna alkaloid, which is isolated from the traditional Chinese medicinal herb Salvia miltiorrhiza belonging to the Solanaceae family [50,51]. It is mainly used to relieve circulatory diseases in clinical conditions such as disseminated intravascular coagulation (DIC) and skeptic shock [52,53]. The research of Yu et al [54] showed that anisodamine activated a 7 nicotinic acetylcholine receptor (a7nAChR) to increase the level of serum estradiol.…”
Section: Anisodaminementioning
confidence: 99%
“…Anisodamine is a belladonna alkaloid, which is isolated from the traditional Chinese medicinal herb Salvia miltiorrhiza belonging to the Solanaceae family [50,51]. It is mainly used to relieve circulatory diseases in clinical conditions such as disseminated intravascular coagulation (DIC) and skeptic shock [52,53]. The research of Yu et al [54] showed that anisodamine activated a 7 nicotinic acetylcholine receptor (a7nAChR) to increase the level of serum estradiol.…”
Section: Anisodaminementioning
confidence: 99%
“…[7]. It has been used for many diseases, such as respiratory diseases, various circulatory disorders, septic shock, gastric ulcers, migraine, gastrointestinal colic, acute glomerular nephritis, eclampsia, rheumatoid arthritis, obstructive jaundice, opiate addiction, organophosphorus poisoning, and snake bite, as well as in radiation damage protection, due to its ability to improve microcirculation [8,9]. Anisodamine had also been used to treat patients of severe acute respiratory syndrome (SARS) with hypoxemia in 2003 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that 6β-hydroxyhyoscyamine (2) (anisodamine), the biosynthetic intermediate between hyoscyamine (1) and scopolamine (3), has the lowest neurotoxicity, suggesting this drug as new therapeutic agent against Alzheimer's disease and organophosphate poisoning. 3 Despite their beneficial pharmaceutical properties and high therapeutic demand, the lack of high yielding and stereospecific total synthesis approaches, requires the production of 1-3 to rely on plant ex-traction. 1,4 Therefore the exploration of new reliable plant sources is of crucial interest.…”
Section: Introductionmentioning
confidence: 99%